Discovery of Highly Trimethoprim-Resistant DfrB Dihydrofolate Reductases in Diverse Environmental Settings Suggests an Evolutionary Advantage Unrelated to Antibiotic Resistance - Stella Cellier-Goetghebeur; Kiana Lafontaine; Claudèle Lemay-; Princesse Tsamo; Alexis Bonneau-Burke; Janine N. Copp; Joelle N. Pelletier (MDPI AG, 2022)
Type B dihydrofolate reductases (DfrB) are intrinsically highly resistant to the widely used antibiotic trimethoprim, posing a threat to global public health. The ten known DfrB family members have been strongly associated with genetic material related to the application of antibiotics. Several dfrB genes were associated with multidrug resistance contexts and mobile genetic elements, integrated both in chromosomes and plasmids. However, little is known regarding their presence in other environments. Here, we investigated the presence of dfrB beyond the traditional areas of enquiry by conducting metagenomic database searches from environmental settings where antibiotics are not prevalent. Thirty putative DfrB homologues that share 62 to 95% identity with characterized DfrB were identified. Expression of ten representative homologues verified trimethoprim resistance in all and dihydrofolate reductase activity in most. Contrary to samples associated with the use of antibiotics, the newly identified dfrB were rarely associated with mobile genetic elements or antibiotic resistance genes. Instead, association with metabolic enzymes was observed, suggesting an evolutionary advantage unrelated to antibiotic resistance. Our results are consistent with the hypothesis that multiple dfrB exist in diverse environments from which dfrB were mobilized into the clinically relevant resistome. Our observations reinforce the need to closely monitor their progression.